Maslahah Perspective on Husband Nusyuz in Islamic Law and Positive Law In Indonesia - Jayusman Jayusman; Shafra Shafra; Rahmat Hidayat; Efrinaldi Efrinaldi; Badarudin Badarudin (Universitas Islam Negeri Raden Fatah Palembang, 2022)
Abstract: The Qur'an reviews the husband's nusyuz as contained in the letter an-Nisa/4 verse 128. The jurisprudence and positive law literature in Indonesia do not specifically discuss the husband's nusyuz. The discussion is only limited to the wife's nusyuz. This study focuses on the analysis of the husband's maslahah nusyuz in Islamic law and positive law. The conclusions of this study are: Nusyuz’s husband is not fulfilling the rights of the wife or not carrying out the obligations of the husband. The discourse on Islamic law and positive law only focuses on discussing the wife's nusyuz. Nusyuz's husband was resolved in a familial way. If it is considered to bring benefit to both of them, then they can return to living their domestic life. However, if reuniting them does not bring any benefit, then they can file for divorce.